1973
DOI: 10.1002/aic.690190115
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of carrier‐facilitated transport

Abstract: The physical and mathematical characteristics of carrier-facilitated transport in a liquid film are examined for a reaction scheme of the form A + B Fr? AB, in which A is the permeating species and B and AB are diffusable species which are constrained not to leave the film. For thin films, a solution is developed as a perturbation from purely physical diffusion and is expressed as a second-order power series. For thick films, a solution is developed as a perturbation from a state in which the species concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

1974
1974
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(70 citation statements)
references
References 16 publications
3
67
0
Order By: Relevance
“…Smith and applied to the analysis of carrierfacilitated membrane transport [8,9]. The first, which was dubbed "Thin Film Theory," uses regular perturbation methods to account for reaction-induced departures from purely diffusive mass transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Smith and applied to the analysis of carrierfacilitated membrane transport [8,9]. The first, which was dubbed "Thin Film Theory," uses regular perturbation methods to account for reaction-induced departures from purely diffusive mass transfer.…”
Section: Introductionmentioning
confidence: 99%
“…The total F flux from left to right (or toward higher x) is given by: (30) The ratio [maxJ F (x)−minJ F (x)]/J F (x 2 ) is a measure of the accuracy of our numerical solutions. We found that the ratio of flux variation to the mean flux of J F (x) is 10 −4 at most, meaning that the flux of F is virtually constant (and therefore accurate) and that steady state was reached.…”
Section: Resultsmentioning
confidence: 99%
“…Gonzalez-Fernandez and Atta11 used a numerical approach to a similar problem, employing a piece-wise linearization of the equations. Jacquez15 and Smith et al 30 developed numerical and asymptotic methods for the steady-state diffusion problem. Their solution is not restricted to a thin layer, but accounts for only two diffusion coefficients: for the free ligand and for the complex.…”
Section: Introductionmentioning
confidence: 99%
“…(Goddard et al, 1970;Kruezer and Hoofd, 1970;Smith et al, 1973), regular perturbation method (Suchdeo and Schultz, 1974), and techniques involving other approximations to the differential equations (Friedlander and Keller, 1965;Otto and Ouinn, 1971;Donaldson and Ouinn, 1975;Smith and 0uinn, 1979;Hoofd and Kruezer, 1981 Once the initial guesses were generated for all the variables, the problem was solved by DVCPR routine (Guha, 1989 (Chow, 1979). Such iteration formula at the interior grid point (i,j) can be written as…”
Section: Applyingmentioning
confidence: 99%